Comparison of two alternate PGF2α products in two estrus synchronization protocols in beef heifers. (10th April 2018) - Oosthuizen, Nicola; Lansford, Alicia C; Canal, Luara B; Fontes, Pedro L P; Sanford, Carla D; Dahlen, Carl R; DiLorenzo, Nicolas; Funston, Rick N; Lamb, G Cliff
Abstract: Two experiments were conducted to evaluate the effects of a high concentrate, s.c. PGF2α compared with a conventionally concentrated, i.m. PGF2α in estrus synchronization protocols for heifers. In Exp. 1, 869 Angus-based beef heifers were enrolled at 8 locations. All heifers were exposed to the 7-d CO-Synch + controlled internal drug release (CIDR ) estrus synchronization protocol. On day 7 of the protocol heifers received 100 µg of GnRH i.m., and a CIDR insert for 7 d. On day 0, at CIDR removal, estrous detection patches were applied to heifers and, within location, heifers randomly received 1 of 2 PGF2α treatments: 5 mL of Lutalyse i.m. (CONTROL; n = 434) or a 2 mL of Lutalyse HighCon s.c. (HiCON; n = 435). A second GnRH injection was administered at 54 ± 2 h and heifers were fixed-time AI (TAI ). Heifers were evaluated for estrous activity at TAI by determining the activation of estrous detection patches. Pregnancy rates to AI (PR/AI) were diagnosed by transrectal ultrasonography between 35 and 55 d after TAI. The percentage of heifers exhibiting estrus between day 0 and TAI did not differ ( P = 0.68) between CONTROL and HiCON treatments (47 vs. 46 ± 4%, respectively). Additionally, PR/AI were similar ( P = 0.65) between CONTROL and HiCON treatments (46 vs. 45 ± 3%). In Exp. 2, 190 Angus-based beef heifers were enrolled at 2 locations. Heifers were exposed to the melengestrol acetate (MGA )—PGF2α protocol where they were offered 0.5 mg MGA per day from days 1 to 14. On day 33, heifers were randomly assigned to receive CONTROL ( n = 95) or HiCON ( n = 95) treatment, and estrous detection aids were applied. Heifers were exposed to AI 12 h after detection of estrus. Heifers not detected in estrus at location 1 received a second PGF2α injection 6 d after the initial PGF2α injection and were placed with fertile bulls. Heifers at location 2 that did not express estrus were administered 100 µg of GnRH i.m. and exposed to TAI 96 h after the initial PGF2α injection. Transrectal ultrasonography was used to diagnose PR/AI between 51 and 57 d after the initial PGF2α injection. The percentage of heifers exhibiting estrus during the estrus detection period was similar ( P = 0.40) between CONTROL and HiCON treatments (82 vs. 87 ± 4%). Furthermore, PR/AI were similar ( P = 0.62) between CONTROL and HiCON treatments (60 vs. 65 ± 5%). In summary, the 2 concentrations and corresponding routes of administration of PGF2α were similar in efficacy at synchronizing estrus in beef heifers.